TMIC-36. LOCAL TISSUE BIOMARKERS OF RESPONSE TO THERAPY FOR GLIOBLASTOMA. (5th November 2018) - Rajani, Karishma; Olson, Ian; Jacobs, Joshua; Macura, Slobodan; Sarkaria, Jann; Burns, Terry
Abstract: Glioblastoma (GBM) is a common deadly malignant brain cancer of the central nervous system (CNS), with a median survival of 12–15 months. Scientific advancements are lacking in developing effective therapies for both primary GBM, as well as secondary GBMs, that typically originate as malignant transformation of lower-grade isocitrate dehydrogenase (IDH)-mutant tumors. The unique metabolomic profile of IDH-mutant tumors may present opportunities to develop biomarker signatures of therapeutic efficacy. Microdialysis is an extracellular fluid sampling collection technique utilizing a perfused semipermeable catheter to permit diffusion of molecules between brain interstitium and the perfusate. We hypothesized that microdialysis may identify a metabolomics-based biomarker response to therapy in IDH-mutant tumors. To test this hypothesis, orthotopic xenografts were generated from two patient-derived GBM lines harboring mutations in IDH1. Perfusates were collected from intra-cranial tumors in aythmic nude mice sampled at baseline, 24h and 72h time-points post treatment with temozolomide, an oral alkylating agent used to treat IDH-mutant gliomas, compared with vehicle treatment, and TMZ-treated non-tumor bearing animals. Perfusates were analyzed via unsupervised metabolomic profiling using both gas and liquid chromatography-mass spectrometry (GC/LC-MS). Results of metabolic signatures will be presented. This study aims to demonstrate proof-of-principle and the feasibility of using microdialysis as an approach to identify local tissue biomarkers of tumor response to drug therapy. This work will be complemented by parallel analysis of non-IDH-mutant and TMZ-resistant xenografts, as well as signatures of response to other therapies to yield predictive in vivo tissue biomarkers of drug responsiveness translatable to clinical practice.